PERBEDAAN KARAKTERISTIK-KARAKTERISTIK EPIGENETIS UPPER VISCEROCRANIUM DARI SAMPEL TENGKORAK MANUSIA LIANG BUA, LEWOLEBA, MELOLO, DAN NTODO LESEH (NUSA TENGGARA TIMUR) DAN GILIMANUK (BALI) - Rusyad Adi Suriyanto (BRIN, 2007)
This study aims to determine the differences in the epigenetic characteristics of the upper viscerocranium from human skull samples Liang Bua, Lewoleba, Melolo and Ntodo Leseh (East Nusa Tenggara) and Gilimanuk (Bali), and the factors that determine and influence them. The research subjects included the upper viscerocranium from samples of adult human skulls from the Late Neolithic transition period to the Paleometallic Age with an annuity of about 1500-4000 years.